Highly efficient generation of glutamatergic/cholinergic NT2-derived postmitotic human neurons by short-term treatment with the nucleoside analogue cytosine β-d-arabinofuranoside - González-Burguera, Imanol; Ricobaraza, Ana; Aretxabala, Xabier; Barrondo, Sergio; García del Caño, Gontzal; López de Jesús, Maider; Sallés, Joan (Stem cell research, 2016)
The human NTERA2/D1 (NT2) cells generate postmitotic neurons (NT2N cells) upon retinoic acid (RA) treatment and are functionally integrated in the host tissue following grafting into the rodent and human brain, thus representing a promising source for neuronal replacement therapy. Yet the major limitations of this model are the lengthy differentiation procedure and its low efficiency, although recent studies suggest that the differentiation process can be shortened to less than 1week using nucleoside analogues. To explore whether short-term exposure of NT2 cells to the nucleoside analogue cytosine β-d-arabinofuranoside (AraC) could be a suitable method to efficiently generate mature neurons, we conducted a neurochemical and morphometric characterization of AraC-differentiated NT2N (AraC/NT2N) neurons and improved the differentiation efficiency by modifying the cell culture schedule. Moreover, we analyzed the neurotransmitter phenotypes of AraC/NT2N neurons. Cultures obtained by treatment with AraC were highly enriched in postmitotic neurons and essentially composed of dual glutamatergic/cholinergic neurons, which contrasts with the preferential GABAergic phenotype that we found after RA differentiation. Taken together, our results further reinforce the notion NT2 cells are a versatile source of neuronal phenotypes and provide a new encouraging platform for studying mechanisms of neuronal differentiation and for exploring neuronal replacement strategies. [Display omitted] •NT2 cells differentiate into human postmitotic neurons by short-term treatment with AraC.•Increase in confluence at mid-point of AraC treatment yielded higher differentiation efficiency.•AraC-differentiated neurons display a dual glutamatergic/cholinergic phenotype.